2015
DOI: 10.1111/ajt.13396
|View full text |Cite
|
Sign up to set email alerts
|

Primary Cytomegalovirus Infection Significantly Impacts Circulating T Cells in Kidney Transplant Recipients

Abstract: Cytomegalovirus (CMV) infection profoundly affects the T cell compartment and is associated with alterations in T cell aging parameters and generation of cytotoxic CD4þ CD28null T cells. Hence, the effect of a primary CMV infection post-kidney transplantation (KT) on the peripheral T cell compartment was examined. As aging parameters, we determined the T cell differentiation status, T cell receptor excision circle (TREC) content, CD31þ na€ ıve T cell numbers and relative telomere length (RTL) pre-KT and 12 mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 44 publications
3
23
0
Order By: Relevance
“…This subset highly expressed endothelial homing marker CX3CR1 and exhibited cytotoxic function against endothelial cells in an NKGD2‐dependent manner. Furthermore, in concordance with a recent study on primary CMV infection post–kidney transplant , high frequency of CD4+CD28‐negative population was associated with decline in eGFR at 1 year posttransplant and an increased rate of delayed graft function, though it is unclear whether this observation is related or not to direct immune injury to the graft.…”
Section: Belatacept Resistance and T Cellssupporting
confidence: 83%
“…This subset highly expressed endothelial homing marker CX3CR1 and exhibited cytotoxic function against endothelial cells in an NKGD2‐dependent manner. Furthermore, in concordance with a recent study on primary CMV infection post–kidney transplant , high frequency of CD4+CD28‐negative population was associated with decline in eGFR at 1 year posttransplant and an increased rate of delayed graft function, though it is unclear whether this observation is related or not to direct immune injury to the graft.…”
Section: Belatacept Resistance and T Cellssupporting
confidence: 83%
“…Following CMV infection, populations of CD57 + T cells expand and exhibit polyfunctional responses . Similar expansions of memory T cells are observed in CMV‐seropositive patients with end‐stage renal disease or transplant recipients with primary CMV infection , but renal transplant patients have an extended life expectancy and a high burden of CMV. In this context, it is yet unclear whether intermittent CMV reactivation or latent CMV expand memory T cells with higher functionality or leads to their exhaustion, with a loss of cytotoxic activity and production of TNFα and IL‐2 .…”
Section: Introductionmentioning
confidence: 74%
“…The different posttransplant T cell dynamics were clearly caused by the infections. The significant rise in CD8 + CD28 null T cell percentage in the infection group, for example, was most likely caused by a primary CMV infection (4,8,37). A study by Calarota et al showed that the drop in CD4 + T cells coincided with the peak of OIs (28).…”
Section: Discussionmentioning
confidence: 98%